Strategies on sustaining feedback in a technology integrated learning environment (tile) / Ng Huey Zher - Ng, Huey Zher (2016)
Feedback has been lauded as the pedagogical tool in higher education. Studies have shown feedback in classroom implementation remains an ongoing challenge. Based on past and current literature, the challenges in sustaining feedback can be mainly identified into three arguments; (1) assignments which do not allow feed forward (2) large classes (3) student’s undervalued perceptions of feedback. On the other hand, effective strategies to contain the issues at hand were also discussed in the literature. Unfortunately, there is a lack of research regarding sustaining feedback on the three identified issues within a technology integrated learning environment (TILE). The objectives of the research are, therefore: 1. To examine instructional strategies which sustain feedback for TILE 2. To identify the challenges occurred during feedback implementation in the developed TILE Design and development research (DDR) is selected as the research design for this project. DDR is also the preferred research design because it is an applied type of research. Under the category of product and tool research, DDR recognizes the influence of the work environments. This is important because the area of study requires the collection of authentic data in “real-world” settings for contribution to the feedback practice. The students of a course were the samples for this study. The instruments used for this study are questionnaire, observation and interview. In the data analysis, the following strategies for sustaining feedback received positive response from the students: Duration for feedforward; Feedback as an evaluated item in an assignment; Appropriate digital tools; Creating main groups and sub groups for iterative feedback; Prompt and constant flow feedback; Constructive, concise, focused and meaningful to feed-forward and feedback loop. At the same time, there were challenges which occurred during the implementation of sustaining v feedback. With the challenges, came the reminders of what needed to be avoided or adapted in the strategies for sustaining feedback in TILE. The implications of the research is that the strategies to sustain feedback in TILE need to (1) have social constructivist as its theoretical base, (2) be designed around the coursework of the subject, and (3) include active participation from the lecturers.